PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PT DHARMA SAMUDERA FISHING INDUSTRIES, Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA - Velita, Septiany; Siahaan, Yansen; Jubi, Jubi; Ervina, Nelly (SULTANIST: Jurnal Manajemen dan Keuangan, 2019)
The purpose of the research is to find description of liquidity, capital structure, profitability, and firm value, the influence of liquidity and capital structure to the profitability, and the influence of profitability to the firm value at PT Dharma Samudera Fishing Industries, Tbk listed in Indonesia Stock Exchange. The research used descriptive qualitative analysis and descriptive quantitative analysis. Data collection is done by using documentation method. The analysis technique used is the classical assumption test, multiple linear regression analysis, simple linear regression analysis, correlation coefficient, determination coefficient, and hypotesis testing. The data analysis was carried out using the IBM SPSS Statistic program version 20.The result of this research show that 1. Based on the first hypotesis testing, liquidity and capital structure have a significant effect to profitability. 2. Based on the second hypotesis testing, liquidity has no significant effect, but capital structure has significant effect to profitability. 3. Based on the third hypotesis testing, profitability has significant effect to firm value. The suggestions of this research is that company should control the liquid assets to increase profit, manage the long term debt, increase sales, and minimize the operational expenses. Furthermore, for the next researchers needs to research the other factor that effect the firm value.Â Keywords: Liquidity, Capital Structure, Profitability, and Firm Value.